Pengaruh Lingkungan Sekolah Terhadap Prestasi Belajar Siswa Kelas 6 SDN Priuk Ciruas Kota Serang - Alya Aprilia Aziza; Desty Endrawati Subroto; Alya Citra Wulandari; Irodati Karimah; Zahra Fadla Amalia (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
This study aims to determine the influence of the school environment on the academic performance of sixth-grade students at SDN Priuk. The school environment includes physical, social, and psychological aspects that are interconnected in shaping students' learning quality. This research employs a qualitative approach through literature review, direct observation, and interviews with teachers, students, and parents. The results indicate that physical factors such as cleanliness, classroom comfort, and learning facilities significantly affect students' concentration and enthusiasm for learning. In addition, a positive social environment—marked by harmonious relationships among students, teachers, and peers—encourages enjoyable learning interactions and supports student motivation. The psychological aspect also plays a crucial role; students who feel emotionally supported and recognized for their achievements tend to have higher intrinsic motivation and better academic performance. This study recommends that schools continuously improve the quality of the learning environment in all three aspects to create a more conducive atmosphere for students’ academic growth and success..